Implementation of Law Number 23 of 2006 Concerning Population Administration Related to Marriage Certificate Registration in Sanur Urban Village - AA Sagung Mas Thasyatha Anggitha Putra; A.A.A.Ngr. Sri Rahayu Gorda (Borong Newinera Publisher, 2023)
Generally the registration of marriage as a state recognition of its people and to obtain legal certainty and civil rights of the community. Based on this, the issues raised are How to Implement Law No. 23 of 2006 concerning Population Administration related to Registration of Marriage Certificates in Sanur Village and What are the factors that are obstacles in the Implementation of Law No. 23 of 2006 concerning Population Administration related to Registration of Marriage Certificates in Sanur Village. The research method used is an empirical legal research method, using primary data types and secondary data which are further analyzed qualitatively descriptively. The results of research that has been done conclude that first, marriage that is not recorded will cause harm to certain parties. The resulting consequences of not noted marriage where the married couple did not have authentic evidence that they had carried out a legal marriage. As a result, judging from the juridical aspect, the marriage is not recognized by the government, so it does not have legal force (no legal force). Second, the factors on the implementation of the Population Administration (implementation of the Marriage Act) carried out in Sanur village have not been able to realize the Administration Order, have not fully run well because of the legal factors themselves, Law Enforcement factors, supporting facilities or facilitation factors, community factors, and cultural factors.